L’estetica del digitale e le matrici delle politiche culturali europee - Manera, Lorenzo (Aesthetica Preprint, 2023)
Several documents published by the European Commission in the last years concern the topic of digital humanities. In particular, the document “Contribution of the Creative Europe Programme to fostering Creativity and Skills Development in the Audiovisual Sector” and the one titled “Council conclusions on promoting access to culture via digital means with a focus on audience development” highlighted the importance of the promotion of skills related to a critical and active use of digital technologies. A further purpose indicated in the aforementioned documents is to design pathways that can qualify emerging technologies as devices capable of fostering the active role that different types of audiences can play, supporting an elaborative dimension of the skills related to the enjoiment of cultural contents. These aims can be configured within a conceptual framework that contributes to making explicit the relevance of issues related to the field of Aesthetics within the cultural policies promoted by the European Union. Through the examination of some theoretical issues that concern the relationship between visual culture, aesthetics and digital humanities, this contribution aims at outlining the primary connection between the European cultural policies and the contemporary aesthetic debate.